Research on aerodynamic characteristics and control method of rigid-flexible variable camber wing - Tao Xin; Bin Li (Scientific Reports)
Abstract In order to realize the continuous chord bending of the wing and consider the material deformation limitation, a trailing-edge curvature variable wing section combining rigid and flexible structures is proposed. In the wing configuration design, the optimal lift-to-drag ratio is used as the optimization objective, and the wing section mean line is parameterized to obtain the optimal rigid-flexible hybrid deformation configuration. The aerodynamic characteristics of hybrid rigid-flexible deflection wing and traditional rigid deflection wing were compared by flow field calculation. Under different angles of attack, the hybrid deflection airfoil has better aerodynamic performance, with the lift coefficient increasing by up to 1.66 times and the lift-to-drag ratio increasing by up to 2.86 times. Under various flight conditions, the rigid-flexible hybrid wing requires a smaller deflection angle and a better wing configuration than the traditional wing. Under high-angle deflection conditions such as landing, the lift-to-drag ratio of the rigid-flexible hybrid wing is increased by 78%, while delaying flow separation (x/c = 0.8) and reducing trailing-edge vortices, thereby improving aerodynamic efficiency. Additionally, for the flexible deformation part in the rigid-flexible hybrid wing, pneumatic muscles are used as flexible actuators, and a proportional integral sliding mode control method based on a nominal model is established. A test platform was built to control the deformation of the flexible part of the wing rib, and the ability of the flexible part to achieve the target curvature within the range of elastic deformation was verified. The actual deformation curve is very consistent with the target deformation curve. The dynamic performance test of the control method and parameters proves the rationality and effectiveness of the control system design.